Viral dynamics in tropical coastal waters : Effects of warming and nutrient enrichment - Stanley Chai, Choon Yip; Lee, Choon Weng; Lim, Joon Hai; Bong, Chui Wei; Edmund Sim, Ui Hang; Kumaran, Narayanan; Wang, Ai Jun (CSIRO Publishing, 2023)
Context. We studied the virus component in the microbial food-web in the tropical coastal Sunda Shelf waters. Aims. We investigated viral processes, including the lysogenic to lytic shift dynamics with seawater warming and nutrient enrichment. Methods. We sampled nearshore and offshore waters of Peninsular Malaysia to provide a natural trophic gradient for correlational analyses. We also conducted laboratory experiments to investigate the changes in virus production rates and lysogeny, when temperature (range: 25–37°C) and nutrient concentrations (range: 0.1–1.0× marine-broth concentration) were manipulated. Key results. Observations showed site-dependent differences in dissolved inorganic nutrient concentration, Chl-a (0.21–3.54 μgL−1) and bacterial abundance (4.09 × 105−9.41 × 105 cells mL−1), but not in viral abundance (measured as virus-like particles or VLP) (1.04 × 106−2.39 × 106 VLP mL−1) and virus production rates (0.59 × 105−4.55 × 105 VLP mL−1h−1). From laboratory experiments, both warming and nutrient enrichment increased virus production (R2 > 0.651), decreased lysogeny (R2 > 0.743), and resulted in an increase of the viral lysis: bacterial production ratio, and a stronger viral control on bacterial production. Conclusions. Although both seawater warming and nutrient enrichment increased virus production and reduced lysogeny, nutrient enrichment was a more important factor. Implications. The increasing nutrient concentrations in these waters will increase virus production and virus top-down control of bacteria, and drive the ecosystem towards heterotrophy.